Dalbavancin in the Treatment of Bacteremia and Endocarditis in People with Barriers to Standard Care - Leama Ajaka; Emily Heil; Sarah Schmalzle (MDPI AG, 2020)
Introduction: Dalbavancin is an antibiotic administered by intravenous infusion weekly or bi-weekly and is currently FDA-approved only for treatment of skin and soft-tissue infections. It has shown promise, but is not considered the standard of care, for bacteremia and infective endocarditis (IE), which typically require outpatient parenteral antibiotic therapy (OPAT) for prolonged durations. People who inject drugs (PWID) with bacteremia or IE are often perceived as having barriers to OPAT and standard daily-administered antibiotics, prompting off-label use of dalbavancin in this population. Methods: A retrospective review of adult patients receiving at least one dose of dalbavancin for bacteremia or IE was conducted between 1 November 2017 and 31 October 2019. Outcomes and reasons for use of dalbavancin were recorded, including specific barriers to standard therapy. Results: Stated reasons for dalbavancin use in the 18 patients identified included active injection drug use (50%), inability to arrange standard OPAT due to patient adherence or inability to place in skilled nursing facility (SNF) (22%), risk for additional infections or other morbidity with OPAT (22%), and patient preference (6%). In 11 patients (61%) SNF placement was not attempted due to behavioral issues or patient declination. There were five patients who did not complete their intended course of treatment (28%). At 90 days, eight patients (44%) achieved a clinical or biologic cure, six (33%) failed treatment, and four (22%) were lost to follow-up. Conclusion: Dalbavancin may have a role as salvage therapy in the treatment of IE and bacteremia in PWID who have significant barriers to standard treatment.